Co-designing gendered energy innovations for urban informal settlement households in Kenya : a case study of Mathare Valley informal settlement - Anditi, Christer Adelaide (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.